2011
DOI: 10.1162/jocn.2010.21544
|View full text |Cite
|
Sign up to set email alerts
|

The Evolution of Meaning: Spatio-temporal Dynamics of Visual Object Recognition

Abstract: Abstract■ Research on the spatio-temporal dynamics of visual object recognition suggests a recurrent, interactive model whereby an initial feedforward sweep through the ventral stream to prefrontal cortex is followed by recurrent interactions. However, critical questions remain regarding the factors that mediate the degree of recurrent interactions necessary for meaningful object recognition. The novel prediction we test here is that recurrent interactivity is driven by increasing semantic integration demands … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
143
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 113 publications
(163 citation statements)
references
References 70 publications
16
143
1
Order By: Relevance
“…An alternative possibility is that differences in the quality and richness of early-compared with later-acquired semantic representations (Belke et al, 2005;Brysbaert et al, 2000;Steyvers and Tenenbaum, 2005) are reflected in activation of greater numbers of anterior temporal neurons and synapses, resulting in a stronger neuromagnetic response. In either case we note that the time period in which we observed modulation of the semantic response in left anterior temporal cortex by AoA overlaps with the period in which Clarke et al (2011Clarke et al ( , 2013 reported stronger activation of medial left anterior temporal cortex by basic than domain level naming and a modulation of responses at the same site by distinctiveness. It also overlaps with period that Bemis and Pylkkänen (2011) associated with the process of integrating the meanings of pairs of words.…”
Section: Discussionsupporting
confidence: 53%
See 4 more Smart Citations
“…An alternative possibility is that differences in the quality and richness of early-compared with later-acquired semantic representations (Belke et al, 2005;Brysbaert et al, 2000;Steyvers and Tenenbaum, 2005) are reflected in activation of greater numbers of anterior temporal neurons and synapses, resulting in a stronger neuromagnetic response. In either case we note that the time period in which we observed modulation of the semantic response in left anterior temporal cortex by AoA overlaps with the period in which Clarke et al (2011Clarke et al ( , 2013 reported stronger activation of medial left anterior temporal cortex by basic than domain level naming and a modulation of responses at the same site by distinctiveness. It also overlaps with period that Bemis and Pylkkänen (2011) associated with the process of integrating the meanings of pairs of words.…”
Section: Discussionsupporting
confidence: 53%
“…Comparison of responses to pseudohomophones and orthographic controls in the left posterior IFG/precentral gyrus found a stronger response to targets following pseudohomophone than orthographic control primes around 100 ms (30-40 Hz) that was in the induced (non-phase-locked) rather than the evoked (phase-locked) component, with additional modulations between 200 and 500 ms in both the evoked and the induced components. Clarke et al (2011) used MEG data from a study of object naming to argue for on-line interactions between posterior visual and anterior semantic processing. Participants named pictures of objects at either a domain level (saying "living" or "manmade" in response to the pictures) or at a basic level (e.g., saying "cow" or "hammer").…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations